2006
DOI: 10.1080/01904160600972563
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Requirements of Rice Grown in Soils With Different Sodicity

Abstract: Phosphorus (P) fertilization is reported to alleviate the adverse effects of sodicity on survival of the seedlings, growth, and yield of rice. However, it is not known if required levels of Olsen's P to alleviate the adverse sodicity effects varies with increased sodicity stress. The present study, conducted at various pH values (8.0, 9.3, 9.7, and 9.9) with varying levels of P fertilization (P0.0, P0.2, P0.4, P0.6, and P0.8 kg hm −2 ), showed that P requirements of rice increased with increases in sodicity st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Whereas, higher salt concentrations (100, 200 mmol·dm -3 NaCl) resulted in significant decline in phosphorus level in plant tissues. Some scientists have suggested that application of phosphorus might improve tolerance of plant to drought and salinity (Goutierrez-Boem and Thomas 1998; Kaya et al 2001;Burman et al 2004;Qadar and Ansari 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, higher salt concentrations (100, 200 mmol·dm -3 NaCl) resulted in significant decline in phosphorus level in plant tissues. Some scientists have suggested that application of phosphorus might improve tolerance of plant to drought and salinity (Goutierrez-Boem and Thomas 1998; Kaya et al 2001;Burman et al 2004;Qadar and Ansari 2006).…”
Section: Discussionmentioning
confidence: 99%